2004
DOI: 10.1128/aac.48.9.3407-3411.2004
|View full text |Cite
|
Sign up to set email alerts
|

Paradoxical Effect of Caspofungin: Reduced Activity against Candida albicans at High Drug Concentrations

Abstract: Resistance problems with caspofungin, an echinocandin inhibitor of fungal cell wall glucan synthesis, have been rare. We noted paradoxical turbid growth of Candida albicans isolates in broth in some high (supra-MIC) concentrations. Among isolates submitted for susceptibility testing and screened at drug concentrations up to 12.5 g/ml, the frequency was 16%. Analysis of the turbid growth indicated slowing of growth in the presence of drug but with numbers of CFU up to 72% those of drug-free controls. Clearing o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
169
0
5

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 208 publications
(182 citation statements)
references
References 21 publications
8
169
0
5
Order By: Relevance
“…8,25 This paradoxical effect is similar to that described for Gram-positive bacteria in response to increasing b-lactam drug concentrations (the 'Eagle effect'). 26,27 Interestingly, this resistance to drug-induced inhibition of growth at higher concentrations of CAP is reversible and is more pronounced among Candida species; 25 the echinocandin-pneumocandin-Eagle effect is less pronounced with filamentous molds, although in experimental animal models of brain zygomycosis lower CAP concentration favorable effect was reversed by increasing the concentration of the drug leading to reduced High-dose caspofungin therapyresponse.…”
Section: Discussionsupporting
confidence: 50%
“…8,25 This paradoxical effect is similar to that described for Gram-positive bacteria in response to increasing b-lactam drug concentrations (the 'Eagle effect'). 26,27 Interestingly, this resistance to drug-induced inhibition of growth at higher concentrations of CAP is reversible and is more pronounced among Candida species; 25 the echinocandin-pneumocandin-Eagle effect is less pronounced with filamentous molds, although in experimental animal models of brain zygomycosis lower CAP concentration favorable effect was reversed by increasing the concentration of the drug leading to reduced High-dose caspofungin therapyresponse.…”
Section: Discussionsupporting
confidence: 50%
“…Paradoxical growth of Candida isolates at echinocandin concentrations that exceed the MIC is well recognized in vitro (23,25). In the present study, we characterized echinocandin par- The ranges of drug concentrations tested were as follows: caspofungin (0.06 to 64 g/ml), cyclosporine (0.0025 to 10.25 g/ml), nikkomycin Z (2 to 128 g/ml), and tacrolimus (0.0025 to 10.25 g/ml).…”
Section: Discussionmentioning
confidence: 99%
“…Along these lines, concerns have been expressed about the possible therapeutic implications of an in vitro paradoxical effect, in which certain Candida isolates exhibit increased growth in the presence of echinocandin concentrations above the minimum inhibitory concentration (MIC). Although the paradoxical effect is typically apparent in vitro at concentrations that are achievable in human serum with conventional dosing strategies, the clinical relevance of the phenomenon in the treatment of patients with candidiasis is unproven.To date, paradoxical effects have been demonstrated against Candida albicans, C. parapsilosis, C. krusei, C. tropicalis, and C. dubliniensis isolates (3,5,10,16,23,25,28). Moreover, they have been described with all three commercially available echinocandins (5), although rates differ among these agents.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…To the editor, In their article regarding the paradoxical growth effect with echinocandins, Fleischhacker et al [1], discussing their findings with caspofungin, state: "Stevens et al did not demonstrate [a paradoxical effect, i.e., growth in concentrations above an apparent MIC] in a … group of C. albicans isolates…," citing two of our papers [2,3]. However, in our original description of the paradoxical effect with caspofungin [2], we reported the phenomenon in two sets of C. albicans isolates, 16% of 25 isolates and 18% of 17 isolates, and in the later paper studying the mechanism [3], we had expanded the study of frequency to 65 isolates, of which 22% had shown the effect.…”
mentioning
confidence: 99%